2018
DOI: 10.1002/chem.201804325
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bis(arylethynyl)pyrrolo[3,2‐b]pyrroles and Effect of Intramolecular Charge Transfer on Their Photophysical Behavior

Abstract: 3,6-Bis(arylethynyl)pyrrolo [3,2-b]pyrroles were synthesizedt hroughatwo-step procedure involving double direct alkynylation of the electron-rich core followed by Sonogashira coupling. In comparison with the parentt etraarylo-pyrrolo[3,2-b]pyrroles and benzo-fusedp yrrolopyrroles, these new dyes showed moderately redshifted absorption. Almosta ll derivatives showedp ositivef luorescence solvatochromism and, for the first time, red-emitting pyrrolopyrroles were obtained.C omputationals tudies revealedt hat, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 92 publications
2
26
0
Order By: Relevance
“…Comparison of the one-photon absorption (OPA) and TPA spectra in conjunction with quantum-chemical calculations reported in Ref. [44] points to mutually exclusive selection rules, namely large OPA and weak TPA S 1 ! S 0 cross-sections and weak OPA and large TPA S 2 !…”
Section: Basic Photophysical Propertiesmentioning
confidence: 88%
See 3 more Smart Citations
“…Comparison of the one-photon absorption (OPA) and TPA spectra in conjunction with quantum-chemical calculations reported in Ref. [44] points to mutually exclusive selection rules, namely large OPA and weak TPA S 1 ! S 0 cross-sections and weak OPA and large TPA S 2 !…”
Section: Basic Photophysical Propertiesmentioning
confidence: 88%
“…The synthesis of dyes 1-4 was described in reference [44]. Tetrachloroethylene (TCE, purum, > 99.0 %) and p-xylene (PXY, puriss.…”
Section: Experimental Section Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their use as scaffolds for the synthesis of heterocyclic analogues of large curved polycyclic aromatic hydrocarbons has also been investigated . Although it still remains a challenge to bathochromically shift the fluorescence in this group of dyes while maintaining strong emission intensity, we have recently reported the photoluminescent color‐tuning of pyrrolo[3,2‐ b ]pyrrole derivatives from cyan to yellow emission by co‐crystallization methods. This was achieved through co‐crystallization of a pyrrolo[3,2‐ b ]pyrrole possessing two pyridine moieties with various Brønsted acids, such as phenols, carboxylic acids, and sulfonic acid, and we found that the degree of protonation affects the photoluminescent properties .…”
Section: Introductionmentioning
confidence: 99%